Comparative Cost-Effectiveness of Stereotactic Body Radiation Therapy Versus Intensity-Modulated and Proton Radiation Therapy for Localized Prostate Cancer - Parthan, Anju; Pruttivarasin, Narin; Davies, Diane; Taylor, Douglas; Pawar, Vivek; Bijlani, Akash; Hassmiller Lich, Kristen; Chen, Ronald (Frontiers in Oncology, 2012)
Objective. To determine the cost-effectiveness of several external beam radiation treatment modalities for the treatment of patients with localized prostate cancer. Methods. A lifetime Markov model incorporated the probabilities of experiencing treatment-related long-term toxicity or death. Toxicity probabilities were derived from published sources using meta-analytical techniques. Utilities and costs in the model were obtained from publically available secondary sources. The model calculated quality-adjusted life expectancy and expected lifetime cost per patient, and derived ratios of incremental cost per quality-adjusted life year (QALY) gained between treatments. Analyses were conducted from both a payer and societal perspectives. One-way and probabilistic sensitivity analyses were performed. Results. Compared to intensity modulated radiation therapy (IMRT) and proton beam therapy (PT), stereotactic body radiation therapy (SBRT) was less costly and resulted in more QALYs. Sensitivity analyses showed that the conclusions in the base-case scenario were robust with respect to variations in toxicity and cost parameters consistent with available evidence. At a threshold of $50,000/QALY, SBRT was cost effective in 75%, and 94% of probabilistic simulations compared to IMRT and PT, respectively, from a payer perspective. From a societal perspective, SBRT was cost-effective in 75%, and 96% of simulations compared to IMRT and PT, respectively, at a threshold of $50,000/QALY. In threshold analyses, SBRT was less expensive with better outcomes compared to IMRT at toxicity rates 23% greater than the SBRT base-case rates. Conclusions. Based on the assumption that each treatment modality results in equivalent long-term efficacy, SBRT is a cost-effective strategy resulting in improved quality-adjusted survival compared to IMRT and PT for the treatment of localized prostate cancer.